Solve the following equation: ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2}$.
Answer
Verified
515.1k+ views
Hint: Here, we will proceed by replacing $x$ by $\dfrac{1}{x}$in the given equation in order to prove that it will come out as the same.
Given, equation is ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2} \Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0{\text{ }} \to {\text{(1)}}$
Let us replace $x$ by $\dfrac{1}{x}$ in equation (1), we get
$
\Rightarrow {\left( {\dfrac{1}{x}} \right)^4} - 3{\left( {\dfrac{1}{x}} \right)^3} - 2{\left( {\dfrac{1}{x}} \right)^2} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{1}{{{x^4}}} - \dfrac{3}{{{x^3}}} - \dfrac{2}{{{x^2}}} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{{1 - 3x - 2{x^2} - 3{x^3} + {x^4}}}{{{x^4}}} = 0 \\
\Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0 \\
$
Clearly, the above equation which is obtained by replacing $x$ by $\dfrac{1}{x}$in the given equation (1) is the same as the given equation (1).
As, we know that when in a polynomial of degree four (having two roots as $\alpha $ and $\beta $ ) if $x$ is replaced by $\dfrac{1}{x}$ and the polynomial comes out to be same as previous one then the other two roots of that polynomial will be $\dfrac{1}{\alpha }$ and $\dfrac{1}{\beta }$.
Also, for any general polynomial of degree four \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]
\[
{\text{Sum of all the roots}} = - \dfrac{b}{a} \\
{\text{Sum of product of different roots taken two at a time }} = \dfrac{c}{a} \\
\]
According to the given equation (1), we can say \[a = 1\],\[b = - 3\],\[c = - 2\],\[d = - 3\]and \[e = 1\].
Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{{\left( { - 3} \right)}}{1} = 3{\text{ }} \to {\text{(2)}}\]
Sum of product of different roots taken two at a time of the given equation (1) is given by
\[
\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\left( { - 2} \right)}}{1} = - 2 \\
\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = - 2 \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = - 2 - 2 = - 4 \\
\]
\[ \Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4 \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4{\text{ }} \to {\text{(3)}}\]
Now, equation (2) can be re-arranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]
Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right){\text{ }}\]in equation (3), we get
\[\left[ {3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4\]
Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]
\[
\Rightarrow \left[ {3 - t} \right]t = - 4 \Rightarrow {t^2} - 3t - 4 = 0 \Rightarrow {t^2} + t - 4t - 4 = 0 \Rightarrow t\left( {t + 1} \right) - 4\left( {t + 1} \right) = 0 \\
\Rightarrow \left( {t + 1} \right)\left( {t - 4} \right) = 0 \\
\]
\[ \Rightarrow t = - 1\] or \[t = 4\]
\[\beta + \dfrac{1}{\beta } = - 1 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - 1 \Rightarrow {\beta ^2} + \beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( 1 \right) \pm \sqrt {{{\left( 1 \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{ - 1 \pm \sqrt {1 - 4} }}{2} = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\] or \[\beta + \dfrac{1}{\beta } = 4 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = 4 \Rightarrow {\beta ^2} - 4\beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 4} \right) \pm \sqrt {{{\left( { - 4} \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{4 \pm \sqrt {16 - 4} }}{2} = \dfrac{{4 \pm 2\sqrt 3 }}{2} = 2 \pm \sqrt 3 \]
Hence, \[\beta = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]or \[\beta = 2 \pm \sqrt 3 \]
Using equation (2) put the value of \[\beta \], we will get the value for \[\alpha \]
\[\alpha = 2 \pm \sqrt 3 \]or \[\alpha = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]
Therefore, all the roots of the given are \[2 \pm \sqrt 3 \], \[\dfrac{{ - 1 \pm i\sqrt 3 }}{2}\].
Note: These types of problems are solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get them.
Given, equation is ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2} \Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0{\text{ }} \to {\text{(1)}}$
Let us replace $x$ by $\dfrac{1}{x}$ in equation (1), we get
$
\Rightarrow {\left( {\dfrac{1}{x}} \right)^4} - 3{\left( {\dfrac{1}{x}} \right)^3} - 2{\left( {\dfrac{1}{x}} \right)^2} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{1}{{{x^4}}} - \dfrac{3}{{{x^3}}} - \dfrac{2}{{{x^2}}} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{{1 - 3x - 2{x^2} - 3{x^3} + {x^4}}}{{{x^4}}} = 0 \\
\Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0 \\
$
Clearly, the above equation which is obtained by replacing $x$ by $\dfrac{1}{x}$in the given equation (1) is the same as the given equation (1).
As, we know that when in a polynomial of degree four (having two roots as $\alpha $ and $\beta $ ) if $x$ is replaced by $\dfrac{1}{x}$ and the polynomial comes out to be same as previous one then the other two roots of that polynomial will be $\dfrac{1}{\alpha }$ and $\dfrac{1}{\beta }$.
Also, for any general polynomial of degree four \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]
\[
{\text{Sum of all the roots}} = - \dfrac{b}{a} \\
{\text{Sum of product of different roots taken two at a time }} = \dfrac{c}{a} \\
\]
According to the given equation (1), we can say \[a = 1\],\[b = - 3\],\[c = - 2\],\[d = - 3\]and \[e = 1\].
Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{{\left( { - 3} \right)}}{1} = 3{\text{ }} \to {\text{(2)}}\]
Sum of product of different roots taken two at a time of the given equation (1) is given by
\[
\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\left( { - 2} \right)}}{1} = - 2 \\
\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = - 2 \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = - 2 - 2 = - 4 \\
\]
\[ \Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4 \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4{\text{ }} \to {\text{(3)}}\]
Now, equation (2) can be re-arranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]
Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right){\text{ }}\]in equation (3), we get
\[\left[ {3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4\]
Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]
\[
\Rightarrow \left[ {3 - t} \right]t = - 4 \Rightarrow {t^2} - 3t - 4 = 0 \Rightarrow {t^2} + t - 4t - 4 = 0 \Rightarrow t\left( {t + 1} \right) - 4\left( {t + 1} \right) = 0 \\
\Rightarrow \left( {t + 1} \right)\left( {t - 4} \right) = 0 \\
\]
\[ \Rightarrow t = - 1\] or \[t = 4\]
\[\beta + \dfrac{1}{\beta } = - 1 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - 1 \Rightarrow {\beta ^2} + \beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( 1 \right) \pm \sqrt {{{\left( 1 \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{ - 1 \pm \sqrt {1 - 4} }}{2} = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\] or \[\beta + \dfrac{1}{\beta } = 4 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = 4 \Rightarrow {\beta ^2} - 4\beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 4} \right) \pm \sqrt {{{\left( { - 4} \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{4 \pm \sqrt {16 - 4} }}{2} = \dfrac{{4 \pm 2\sqrt 3 }}{2} = 2 \pm \sqrt 3 \]
Hence, \[\beta = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]or \[\beta = 2 \pm \sqrt 3 \]
Using equation (2) put the value of \[\beta \], we will get the value for \[\alpha \]
\[\alpha = 2 \pm \sqrt 3 \]or \[\alpha = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]
Therefore, all the roots of the given are \[2 \pm \sqrt 3 \], \[\dfrac{{ - 1 \pm i\sqrt 3 }}{2}\].
Note: These types of problems are solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get them.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE